West Side story [videorecording (DVD)] - Wise, Robert, 1914-2005; Robbins, Jerome; Wood, Natalie; Beymer, Richard, 1939-; Bernstein, Leonard, 1918-1990; Moreno, Rita; Chakiris, George (MGM Home Entertainment, 2003)
This musical sets the tragedy of Romeo and Juliet against a backdrop of the rivalry of two street gangs, the Sharks and the Jets, in New York of the 1950s. A young woman who is sister to the Sharks leader has her first taste of love with the former head of the Jets.